2000
DOI: 10.1097/00000542-200010000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Neuropathies Associated with Lithotomy Positions

Abstract: In this surgical population, lower extremity neuropathies were infrequent complications that were noted very soon after surgery and anesthesia. None resulted in prolonged disability. The longer patients were positioned in lithotomy positions, the greater the chance of development of a neuropathy. These findings suggest that a reduction of duration of time in lithotomy positions may reduce the risk of lower extremity neuropathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
116
2
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(143 citation statements)
references
References 15 publications
3
116
2
15
Order By: Relevance
“…Differential diagnosis includes the well-described neuropathies known to be associated with the lithotomy position. According to a review by Warner et al, 55 there was a 1.5% incidence of lower extremity neuropathies in patients who underwent general anesthesia and surgery while in the lithotomy position. Positioning the thighs in extreme abduction with external rotation, 56 as is occasionally the case during TVT-O, is a well described risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis includes the well-described neuropathies known to be associated with the lithotomy position. According to a review by Warner et al, 55 there was a 1.5% incidence of lower extremity neuropathies in patients who underwent general anesthesia and surgery while in the lithotomy position. Positioning the thighs in extreme abduction with external rotation, 56 as is occasionally the case during TVT-O, is a well described risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12)(13) PN can develop if the peroneal nerve is compressed between the fibular head and external structures such as an operating table. In our institution, GPs were placed under the knees of LT recipients to reduce lower back strain and prevent contact between the peroneal nerve at the fibular head and a hard surface, according to the recommendation by the Association of periOperative Registered Nurses.…”
Section: Discussionmentioning
confidence: 99%
“…(1,3,5) Most incidences of postoperative PN are associated with surgeries performed in the lithotomy position; postoperative PN is uncommon when the supine position is used. (12,13) In a retrospective review of LT recipients, Moreno et al found that 2 of 143 (1.4%) adult LT recipients developed PN during the postoperative period due to the compression caused by knee supports that were placed in the popliteal space when patients were in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…It is a well-known complication for operation performed in a lithotomy position [6] but is uncommon in supine position. Risk factors for postoperative CPN palsy include prolonged operating time (≥ 4 hours) [7], a light body weight (BMI20) [1,7], a medical history of diabetes mellitus [8] or smoking habits [7].…”
Section: Discussionmentioning
confidence: 99%